Multicultural-Based Islamic Religious Education (PAI) at SMP Sapta Andika Denpasar: Pendidikan Agama Islam (PAI) Berbasis Multikultural di SMP Sapta Andika Denpasar - Hadi , Muhammad Fazlurrahman; Laili, Sofiatul (Halaqa: Islamic Education Journal, 2022)
It is still found that students find it difficult to accept differences, respect others, and do not behave well by applying good morals at school is a separate problem in PAI learning. Especially at SMP Sapta Andika Denpasar-Bali, is unique in the number of Muslim students who are dominant but still provide religious lessons in the other five religions. The purpose of this research is in addition to wanting to know how the management of multicultural-based PAI learning in the school, also what conflict management has been implemented, and the extent to which the level of awareness is tolerant among fellow stakeholders in the school. This type of research is field research, using a descriptive qualitative approach. The findings in this study, Multicultural-Based Islamic Education Learning Planning at SMP Sapta Andika Denpasar do not yet have a specific plan and multicultural values are not listed in detail in the learning tools. However, in practice, PAI teachers have implemented multicultural-based PAI learning, and always link the material with existing facts, this is done so that students are more sensitive to the diverse surrounding environment. Evaluation of multicultural-based Islamic religious education learning at SMP Sapta Andika is by the implementation of multicultural-based PAI learning evaluation which includes three domains, namely cognitive, psychomotor, and affective. Likewise for non-Muslim students who receive adjusted religious education learning, because non-Muslim students already have their religious teacher, then the one who has the right in the assessment is the religious teacher concerned. So the steps that need to be taken, it is necessary to integrate the implementation of multicultural-based Islamic religious education into learning planning.